Accounting narratives and impression management on social media. Issue 6 (19th September 2017) - Yang, Jessica H.; Liu, Siwen
Abstract : In this paper, we examine the defensive and assertive impression management strategies and the impact of firm performance on accounting narratives by investigating the earnings disclosures of FTSE 100 companies on Twitter. Social media has become the prevailing venue for organisational self-presentation because it provides firms with more control over the image they intend to establish and maintain through the communication and content they deliver online. Our findings show that firms minimise the disclosures of negative information but employ various patterns and dissemination techniques to emphasise positive information. Specifically, improving performers are more willing to post and disseminate earnings-related tweets to achieve a higher degree of stakeholder engagement than declining performers. Based on these findings, we conclude that firms present themselves on social media opportunistically to construct a positive public image.